Effects of multi-walled carbon nanotube materials on Ruditapes philippinarum under climate changes: the case of salinity shifts - De Marchi, Lucia (2020)
The toxicity of carbon nanotubes (CNTs) is closely related to their physico-chemical characteristics as well as the physico-chemical parameters of the media where CNTs are dispersed. In a climate change scenario, changes in seawater salinity are becoming a topic of concern particularly in estuarine and coastal areas. Nevertheless, to our knowledge no information is available on how salinity shifts may alter the sensitivity (in terms of biochemical responses) of bivalves when exposed to different CNTs. For this reason, a laboratory experiment was performed exposing the Manila clam Ruditapes philippinarum, one of the most dominant bivalves of the estuarine and coastal lagoon environments, for 28 days to unfunctionalized multi-walled carbon nanotube MWCNTs (Nf-MWCNTs) and carboxylated MWCNTs (f-MWCNTs), maintained at control salinity (28) and low salinity 21. Concentration-dependent toxicity was demonstrated in individuals exposed to both MWCNT materials and under both salinities, generating alterations of energy reserves and metabolism, oxidative status and neurotoxicity compared to non-contaminated clams. Moreover, our results showed greater toxic impacts induced in clams exposed to f-MWCNTs compared to Nf-MWCNTs. In the present study it was also demonstrated how salinity shifts altered the toxicity of both MWCNT materials as well as the sensitivity of R. philippinarum exposed to these contaminates in terms of clam metabolism, oxidative status and neurotoxicity.